Amphiphilic unsymmetrically substituted porphyrin zinc derivatives: synthesis, aggregation behavior of the self-assembled films and NO2 sensing properties. (16th February 2016) - Wu, Yanling; Ma, Pan; Liu, Shanshan; Chen, Yanli
Abstract : The first example of n-type amphiphilic metalloporphyrin-based semiconductors as NO2 sensors is reported. Abstract : Two novel amphiphilic porphyrin derivatives, 5-(benzo-(4-(2-(2-hydroxy)ethoxy)ethoxy))-10, 15, 20-triphenylporphyrinato zinc complex [ZnT(OC2 H4 OC2 H4 OH)PP] (1 ) and 5-(benzo-(4-(2-(4, 10- N, N -15-crown-5)ethoxy)))-10, 15, 20-triphenylporphyrinato zinc complex [ZnT(OC2 H4 NN15C5)PP] (2 ), were designed, synthesized, and characterized by a range of spectroscopic methods. Their electrochemistry was studied by differential pulse voltammetry (DPV). Highly ordered films of1 and2 were fabricated by a solution-based quasi-Langmuir–Shäfer (QLS) technique, and were characterized by electronic absorption spectroscopy, IR spectroscopy, X-ray diffraction, atomic force microscopy (AFM) and current–voltage ( I – V ) measurements. Experimental results revealed that J-type aggregates are formed in the QLS film of1 and2 . The crystallinity and general molecular order in the film of1 were improved more effectively than in2 due to its stronger intermolecular interactions. Furthermore, the conductivity of the QLS film of1 was approximately 1 order of magnitude larger than that of2 . This indicates a significant effect of peripheral groups on the conducting behavior of porphyrins. In addition, the gas sensing behavior of the QLS films of1 and2 toward the electron acceptor gas, NO2, was investigated at concentrations 200 and 800 ppm, respectively. The sensitivity, stability, and reproducibility follow the order1 >2, revealing the effect of intermolecular interaction, film structure/morphology, and low-lying LUMO energy level on sensing performance. Unexpectedly, a decreased current response towards NO2 for the QLS films of both1 and2 was obtained for the first time, which unambiguously demonstrated the n-type semiconducting nature of1 and2 . The present result represents not only the first example of n-type metalloporphyrin-based thin solid films obtained by a solution-based method, but more importantly provides an efficient way to enhance the performance of n-channel organic semiconductors through the combination of molecular design and the film fabrication technique.